2012
DOI: 10.1177/1753193412455790
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome: the association with occupation at a population level

Abstract: The aim of this study was to examine the association of occupation and gender with the incidence and severity of carpal tunnel syndrome (CTS). We examined 884 patients of working age, diagnosed with CTS, in a specialist hand clinic that was the only provider of hand services to a health board area. We categorized occupation using the Standard Occupational Classification 2010 (SOC2010) and used local census data to calculate the incidence in each of the nine major occupational groups. The greatest incidence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…The adjusted HR effect size of 1.3 observed for women in the current study is lower than the approximate doubling of CTS risk observed in other studies 41 42. A study by Silverstein43 found that among those with median neuropathy, women reported more symptoms than men.…”
Section: Discussioncontrasting
confidence: 78%
“…The adjusted HR effect size of 1.3 observed for women in the current study is lower than the approximate doubling of CTS risk observed in other studies 41 42. A study by Silverstein43 found that among those with median neuropathy, women reported more symptoms than men.…”
Section: Discussioncontrasting
confidence: 78%
“…Passive surveillance approaches, such as the use of workers’ compensation data, results in observed annual CTS incidence rates that range from 0.04–0.2 per 100 person-years, varying by occupation or industry (13, 21). Active surveillance approaches, such as the few longitudinal studies that screened all members of a defined cohort for symptoms and nerve conduction abnormalities, results in higher observed CTS incident rates.…”
Section: Discussionmentioning
confidence: 99%
“…Many large epidemiologic studies of electrodiagnostically confirmed CTS have estimated occupational exposure to physical risk factors with imprecise methods such as job titles or self-reported exposures (11, 2021). Conversely, studies using detailed observational or direct methods for quantifying workplace exposures have been limited to smaller samples or single occupations (1415, 2225).…”
mentioning
confidence: 99%
“…For instance, mechanical entrapment of the median nerve at the wrist region, which is known as carpal tunnel syndrome (CTS), results in numbness, pain, and weakness of the muscles innervated by the median nerve [6,41]. CTS is more common among women than men, and can be caused by repeated or highforce manual tasks, especially from vocational exposure [22,37]. As a result of symptoms caused by nerve abnormalities, patients with CTS face difficulties in various hand manipulations needed to perform daily activities, especially those requiring precision grasping [28].…”
Section: Introductionmentioning
confidence: 99%